2013
DOI: 10.1258/ijsa.2012.012102
|View full text |Cite
|
Sign up to set email alerts
|

HLA-B*5701 genetic screening among HIV-1 infected patients in Hong Kong: is this a practical approach in Han-Chinese?

Abstract: Abacavir hypersensitivity is associated with the presence of human leukocyte antigen (HLA)-allele B*5701. However, the cost and workload of routine HLA-B*5701 pretreatment screening is relatively heavy. This study aimed to determine the prevalence of the HLA-B*5701 allele in the HIV-positive population under care in Hong Kong. Blood samples from 1264 HIV-1 infected patients in Hong Kong were collected between 2007 and 2011 for this study. HLA-B*5701 screening of the study group was determined by in-house polym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…Data showed that HLA-B*15:02 prevalence is high among Southeast Asians (allele frequency: 2% to 10%) but low or rare in Koreans, Japanese, and Europeans (allele frequency: 0%-1%) (31). Similar findings were also observed in the association between HLA-B*57:01 induced severe hypersensitivities (32). Therefore, this ethnic difference in the association between HLA alleles and drug-induced hypersensitivity reactions may, at least in part, be explained by the different HLA allele frequencies in different ethnic groups (33).…”
Section: Discussionsupporting
confidence: 66%
“…Data showed that HLA-B*15:02 prevalence is high among Southeast Asians (allele frequency: 2% to 10%) but low or rare in Koreans, Japanese, and Europeans (allele frequency: 0%-1%) (31). Similar findings were also observed in the association between HLA-B*57:01 induced severe hypersensitivities (32). Therefore, this ethnic difference in the association between HLA alleles and drug-induced hypersensitivity reactions may, at least in part, be explained by the different HLA allele frequencies in different ethnic groups (33).…”
Section: Discussionsupporting
confidence: 66%
“…ABC-HSR occurs in 4%-8% of patients receiving abacavir prior to implementation of pre-emptive HLA-B*5701 testing (Hetherington et al, 2001;Mallal et al, 2008). The incidence of ABC-HSR seems to be much higher in Caucasian populations due to a higher frequency of the HLA-B*5701 allele than in non-Caucasian populations (To et al, 2013;Youssoufi et al, 2017;Agbaji et al, 2019).…”
Section: Abacavirmentioning
confidence: 99%
“…Recently, the cost-effectiveness of HLA-B * 57: 01 genotyping related to prescribing abacavir has been questioned, in particular in regions and populations with low prevalence [34,35] . The cost-effectiveness of pharmacogenomic screening is influenced by many factors, with allele frequency and availability of laboratory tests being some of them.…”
Section: Discussionmentioning
confidence: 99%